2021
DOI: 10.1093/ptj/pzab108
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization Exercises Versus Flexion Exercises in Degenerative Spondylolisthesis: A Randomized Controlled Trial

Abstract: Objective Exercise is the mainstay of treatment in patients with low back pain and the first-line option in degenerative spondylolisthesis; however, there is still no consensus surrounding the superiority of any specific exercise program. Thus, the primary aim was to compare the effectiveness of lumbar stabilization exercises and flexion exercises for pain control and improvements of disability in patients with chronic low back pain and degenerative spondylolisthesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Of the 40 RCTs reviewed, 7 were available via open access. Most RCTs ( n = 34, 85.0%) were registered, 25 prospectively 43–67 and 9 retrospectively 68–76 . All RCT registrations were accessible for review.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 RCTs reviewed, 7 were available via open access. Most RCTs ( n = 34, 85.0%) were registered, 25 prospectively 43–67 and 9 retrospectively 68–76 . All RCT registrations were accessible for review.…”
Section: Resultsmentioning
confidence: 99%
“…The protocol was approved by the institute's Ethics and Research Committee prior to commencing the recruitment process in January 2017, and was conducted as a addstudy research in a randomized clinical trial already in the active recruitment phase evaluating the clinical response of the spine stabilization exercises vs flexion exercises (registration number 19/15 and clinicaltrials.gov database (ID NCT02664688). 7 All procedures performed on the participants were in accordance with the Committee's ethical standards and with the 1964 Helsinki Declaration and its later amendments. All participants provided written informed consent before study commencement and received a printed copy for their records.…”
Section: Methodsmentioning
confidence: 99%
“…1,6 In degenerative spondylolisthesis, a previous study demonstrated that lumbar stabilization exercises and flexion exercises offer a similar response for controlling pain and improving disability; however, trophic changes in response to the exercise program were not analyzed. 7 Ultrasound is an increasingly popular and affordable alternative for evaluating the musculoskeletal system, 8 and has proven to be a reliable and accurate tool for the measurement of muscle thickness of the lumbar segment. 9,10 The present study therefore aimed to evaluate-by ultrasound-the changes of the thickness of the main lumbar stabilizing muscles after twelve weeks of performing spine stabilization exercises and to compare these changes with another classical exercise routine (flexion exercises) in patients with CLBP and lumbar spondylolisthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[5,35,36,37] This type of exercise therapy has evolved into a mainstay for treating chronic LBP with focus on core stabilization and muscle coordination. [3,38,39,40,41,42,43]…”
Section: Introductionmentioning
confidence: 99%